2007
DOI: 10.1007/s00270-007-9097-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Radiological Management of Prehepatic Obstruction the Splanchnic Venous System

Abstract: We conclude that interventional procedures can be successfully performed in the majority of patients with obstruction of splanchnic veins, with subsequent improvement of symptoms. Treatment should be customized according to the site and nature of obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…A single session of treatment with PV stent placement may constitute an alternative. Since the early 1990s, only a few case reports or case series addressed stent placement for treatment of benign PV thrombosis [2], stenosis, or occlusion due to chronic or acute pancreatitis [3][4][5][6][7], coagulation disorder [8], or complications related to liver transplantation or other surgeries [9][10][11][12][13]. Stent placement to treat malignant PV lesion has been also evaluated [10,[14][15][16][17][18][19][20][21][22], mainly by Yamakado et al [14][15][16], who published three studies that followed a cohort of patients who presented with biliary or pancreatic neoplasms, and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…A single session of treatment with PV stent placement may constitute an alternative. Since the early 1990s, only a few case reports or case series addressed stent placement for treatment of benign PV thrombosis [2], stenosis, or occlusion due to chronic or acute pancreatitis [3][4][5][6][7], coagulation disorder [8], or complications related to liver transplantation or other surgeries [9][10][11][12][13]. Stent placement to treat malignant PV lesion has been also evaluated [10,[14][15][16][17][18][19][20][21][22], mainly by Yamakado et al [14][15][16], who published three studies that followed a cohort of patients who presented with biliary or pancreatic neoplasms, and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…This is a relatively low-risk procedure, is noninvasive, and if it fails it does not eliminate future surgical options. 21,22 Given the low risk and potentially high yield of these procedures, they can be considered in children without clear indications for surgical intervention that have a favorable anatomy. If this procedure fails, then continued observation seems appropriate for the majority of patients, unless they develop significant complications of portal hypertension.…”
Section: Figurementioning
confidence: 99%
“…The use of TIPS was associated with immediate symptomatic improvement and successful recanalization in 83% of patients treated. 39 Two cases, one with extensive portal, mesenteric and splenic vein thrombosis and another with mesenteric and portal vein thrombosis have been reported to have favorable outcomes with TIPS. 40 A retrospective study on 20 patients with portal vein thrombosis (PVT) suggested a high success rate in cases of non-cavernous PVT and it was effective in prevention of variceal bleeding and recurrent ascites.…”
Section: Interventional Radiological Optionsmentioning
confidence: 99%